The moderating effect of religiosity on intention to use product financing - Faiz, Mochamad Wildan; Firmansyah, Fani (Asian Journal of Islamic Management (AJIM), 2024)
Purpose – This study aimed to determine the effect of financial literacy and word of mouth on the intention to use financing with religiosity as a moderating variable in the BMT UGT Nusantara Capem Pujon.Methodology – This study employs a quantitative approach using primary data collected through accidental sampling. A total of 104 respondents, members of BMT UGT Nusantara Capem Pujon, who use financing products, participated by completing a Likert-scale questionnaire. Data were analyzed using Partial Least Squares (PLS) with SmartPLS version 3.2.9.Findings – The research findings indicate that financial literacy positively influences the intention to use BMT financing products. By contrast, word-of-mouth did not significantly affect this intention. Religiosity moderates the relationship between financial literacy and intention as well as between word-of-mouth and intention.Implications – These findings have several implications for BMT. First, enhancing financial literacy among members can significantly increase their intentions to use financial products. Second, given that word-of-mouth is not a significant factor, BMT should focus more on educational programs rather than relying solely on customer referrals. Finally, integrating religiosity into financial literacy initiatives could further strengthen members' intention to use the BMT's financial products, aligning with their values and beliefs.Originality – The novelty of this study lies in exploring how financial literacy, word of mouth, and religiosity collectively shape the intention to use financing products at BMT UGT Nusantara Capem Pujon, emphasizing the moderating role of religiosity in customized educational strategies to improve financial decisions within Islamic financial institutions.